Phase diagram of the polymeric nitrogen - Yakub, L.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The results of theoretical prediction of the phase transition lines of molecular nitrogen into the polymeric phase at high pressure are presented. The role of the polymeric phase structure in the location of the transition lines on the phase diagram is considered. Possible configuration of the melting curve of the polymeric nitrogen solid forming the polymeric liquid is discussed. Predicted volumes of the coexisting phases are compared with experimental data and with results of the computer simulations.